Mainstreaming the local climate zone framework for climate-resilient cities - Jun Yang; Wenbo Yu; Alexander Baklanov; Baojie He; Quansheng Ge (Nature Communications)
The local climate zone framework is valuable for building climate-resilient cities but is limited in application. This limitation can be resolved by addressing three aspects: transdisciplinary dialog, global atlas construction, and cost–benefit assessment.